40Ar/39Ar biotite and hornblende geochronology from the Oskarshamn area, SE Sweden: Discerning multiple Proterozoic tectonothermal events - Söderlund, Pia; Page, Laurence; Söderlund, Ulf (Geological Magazine, 2008)
Twelve 40Ar-39Ar biotite and four hornblende age determinations have been carried out to constrain the cooling history of the Proterozoic bedrock near Oskarshamn, SE Sweden; an area identified as a possible site for long-term nuclear waste storage. The bedrock hosts 1.80 Ga granites, granodiorites, quartz monzodiorites and diorites/gabbros of the Transscandinavian Igneous Belt and two 1.45-1.44 Ga granite intrusions, the Götemar and Uthammar plutons. Biotite was selected from three surface samples, representing both the older rocks and the younger granites, and from three cored boreholes at nine different depth levels. Hornblende was extracted from samples at the top and bottom of one borehole and at two sub-surface levels of another borehole. Three age groups were distinguished: ≥ 1.62 Ga, 1.51-1.47 Ga and 1.43-1.42 Ga. In the first group, two hornblende analyses yielded ages of 1799±4 Ma and 1773±13 Ma, which indicate initial fast cooling after emplacement of the 1.80 Ga rocks of the Transscandinavian Igneous Belt. Two biotite ages of 1618±7 Ma and 1621±3 Ma are interpreted to date final cooling, through 300 °C, after the youngest suite (1.67 Ga) of the Transscandinavian Igneous Belt in southcentral Sweden. Seven biotite ages, in the range 1.51-1.47 Ga, are enigmatic to interpret but largely coincide with the cessation of widespread rapakivi magmatism in Fennoscandia and the initiation of the Danopolonian event. The 1.44-1.42 Ga hornblende and biotite ages reflect cooling after thermal heating from the 1.45-1.44 Ga Götemar and Uthammar plutons. Later events thermally affected the bedrock in the Oskarshamn area as indicated by a poorly defined biotite age of 928±6 Ma, and other disturbed 40Ar-39Ar ages of samples bordering a complex deformation zone.